Aura Microwave Limb Sounder observations of dynamics and transport during the record-breaking 2009 Arctic stratospheric major warming ... - Manney, Gloria L.; Schwartz, Michael J.; Krüger, Kirstin; Santee, Michelle L.; Pawson, Steven; Lee, Jae N.; Daffer, William H.; Fuller, Ryan A.; Livesey, Nathaniel J. (AGU, 2009)
A major stratospheric sudden warming (SSW) in January 2009 was the strongest and most prolonged on record. Aura Microwave Limb Sounder (MLS) observations are used to provide an overview of dynamics and transport during the 2009 SSW, and to compare with the intense, long-lasting SSW in January 2006. The Arctic polar vortex split during the 2009 SSW, whereas the 2006 SSW was a vortex displacement event. Winds reversed to easterly more rapidly and reverted to westerly more slowly in 2009 than in 2006. More mixing of trace gases out of the vortex during the decay of the vortex fragments, and less before the fulfillment of major SSW criteria, was seen in 2009 than in 2006; persistent well-defined fragments of vortex and anticyclone air were more prevalent in 2009. The 2009 SSW had a more profound impact on the lower stratosphere than any previously observed SSW, with no significant recovery of the vortex in that region. The stratopause breakdown and subsequent reformation at very high altitude, accompanied by ...